City Carbon Budgets : A Proposal to Align Incentives for Climate-Friendly Communities - Salon, Deborah; Sperling, Daniel; Meier, Alan; Murphy, Sinnott; Gorham, Roger; Barrett, James (2012)
Local governments can have a large effect on carbon emissions through land use zoning, building codes, transport infrastructure investments, and support for transportation alternatives. This paper proposes a climate policy instrument--city carbon budgets--that provides a durable framework for local governments to reduce greenhouse gas emissions. Local governments would be assigned an emissions "budget", and would be required to keep annual local transport and buildings emissions within this budget. This policy framework could be implemented and managed by a higher-level government, or might be used in awarding funds to developing country cities from international climate funds. The state of California has enacted a version of this policy. In this paper, we identify and evaluate options for creating an effective and acceptable institutional structure, allocating emission targets to localities, measuring emissions, providing flexibility and incentives to local governments, and assuring compliance. We also discuss the likely costs of such a policy.